The Effect of Anxiety Sensitivity to Loneliness in Hospitalized Children and Adolescents: Multidimensional Models - Pebri Riansyah Claudio Lodra Malhotra; Lina Budiyanti (Jurnal Psikiatri Surabaya, 2024)
Introduction: Although good quality social relationships are essential for every individual’s mental and physical health and well-being, loneliness is an important yet often overlooked social determinant of child and adolescent health. Loneliness felt by a person can put them at risk of anxiety. Anxiety sensitivity is a sensation of fear that will result in physical, social, or psychological problems that later risk clinical anxiety problems. This study aims to determine the effect of anxiety sensitivity on loneliness in children and adolescents who are hospitalized in the hospital. Method: The type of research is quantitative research with an exploratory approach and a self-rating questionnaire. The research subjects were 20 respondents, who were inpatients at the West Java Provincial Mental Hospital. Anxiety was measured using the ASI - 3 (Anxiety Sensitivity Indexes - 3) questionnaire, and the UCLA Loneliness Scale 3 to assess the degree of loneliness. Data were analyzed using simple linear regression with the help of the EPI INFO 7 program. Results: The linear regression test obtained a regression coefficient of 0.786 which states the direction of the influence of variables X and Y is positive with a p-value of 0.000155 <0.05. Conclusion: There is a significant relationship between high anxiety sensitivity and feelings of loneliness in children and adolescents in inpatients. The most experienced dimension of anxiety sensitivity is about social problems while the dominant dimension of loneliness with the choice is always on the dimension of collective connectedness. Keywords: Anxiety Sensitivity, Loneliness, Children and Adolescents